Shape Memory Corrosion-Resistant Polymeric Materials - Nathan D. Jacobson; Jude Iroh (International Journal of Polymer Science)
Shape memory alloys, materials capable of being deformed and maintaining the deformation and additionally capable of returning to the initial position, are valued for a range of applications from actuators to flexible microdevices. Maintaining the properties that make them useful, their ability to deform and reform, requires that shape memory alloys must be protected against corrosion, in which the integration of shape memory polymers can act as a means of protection. Thus, this review is to highlight the utility of self-healing shape memory polymers as a means of corrosion inhibition. Therefore, this review discusses the benefits of utilizing self-healing shape memory polymers for the protection of shape memory, several types of self-healing polymers that could be used, means of improving or tailoring the polymers towards specific usages, and future prospects in designing a shape memory polymer for use in corrosion inhibition.